PECULIARITIES OF RADIATION DIAGNOSTIC OF LUNGS WITH CYSTIC FIBROSIS - Malysh , Artem; Prytkov , Fedir; Morozova , Nataliia; Tkachenko , Mykhailo (The Ukrainian Scientific Medical Youth Journal, 2019)
Our method was used to clarify the possibilities of diagnostic in case of cystic fibrosis and the installation of a computer tomography place in a diagnostic algorithm. Consequently we have analyzed the results of cases of 5 patients at the age from 19 to 25 years with the diagnosis of cystic fibrosis confirmed by sweat samples and genetic investigations. From September 2017 to 2018, the patients were placed in the infection epidemic department No. 2 of Oleksandrivskiy Clinical Hospital die to complications of the main disease. The patients were in the group of middle and high level of severity, respiratory failure II, III stages. These patients were dynamically examined by digital radiography of the chest cavity organs “Radrex” by Toshiba. All of the patients were united by an young age, asthenic and low nutrition body structure, short stature and prolonged anamnesis from early childhood, anamnesis of respiratory diseases, acute respiratory viral infections, bronchitis, sinusitis of the maxillary antrum. It was proved that the results obtained by radiography are typical for CF, but not specific, as well as they could be found in other diffuse lung diseases. After multispiral Computer tomography scan, we have found the main symptoms of cystic fibrosis, such as: total systemic damage of bronchopulmonary structures, two-sides character of pulmonary bronchiectasis . The presence of pronounced dilation of the bronchi of all orders, at least 200% of the original size, with a consolidation and thickening of their walls: a symptom of "ring" and the symptom of "paired strips" and filling of abruptly dilated bronchi of all calibers with a viscous secretion and as a result of this the mucous plugs are formed.Conclusion. The results of the X-ray examination are typical for CF and not specific, as well as for other diffuse pulmonary diseases. Computer tomography can be used for diagnostics of thin structurally functional particles characteristic for cystic fibrosis. It has also been established that the expression of morphological changes of cystic fibrosis are increased with the age of the patients. CT scan is the most useful for the detection morphological and functional changes for cystic fibrosis. Moreover, the CT scan is able to improve the early diagnoses for lungs pathology among the adolescent and the adults, and decrease the period of expectation of the result of the treatment.